Initial bead growth and distribution under low speed icing condition. (March 2020) - Kang, Yu-Eop; Min, Seungin; Kim, Taeseong; Yee, Kwanjung
Highlights: The process of initial bead growth was visualized by image processing technique, and quantitative data was obtained. Initial bead growth properties such as surface coverage and bead size distribution are solely characterized by volume weighted average of bead diameter. The modified scaling approach which consider surface coverage improves the correlation between the initial bead growth properties and icing condition. Abstract: One of the critical issues in recent ice prediction studies is the modeling of roughness formation based on physical phenomena. While a number of experimental studies have been conducted to investigate the fundamental physics of roughness formation, initial bead growth is rarely studied despite its significance to determine bead size and distribution. In the present study, an experiment is conducted to provide physical insight and quantitative data of the initial bead growth. To minimize the uncertainty problem that is inherent in the photographic analysis technique, the experiment was conducted at low speed where beads grow at a more macroscopic scale. In addition, bead identification was conducted through an image processing technique to reduce subjective interpretation. In the data analysis process, the 'characteristic parameter' concept was adopted to represent the bead growth properties simply. It was verified that the parameter can be extended to initial bead growth studies through the acquired bead data. It was also found that surface coverage and bead distribution, which are the critical indicators of the bead growth process, were well characterized by the parameter. Finally, the correlation between characteristic parameters and icing condition was made, by using a scaling method that can implicitly represent the icing condition variable. In the process, the scaling approach was modified to reflect the surface coverage characteristics of the bead growth, and an improvement of the correlation was achieved. It is expected that the correlation acquired from this study contribute to the modeling of roughness formation, and the methods introduced for data analysis can be applied to subsequent studies of initial bead growth.